Enhanced coalbed methane recovery by the modification of coal reservoir under the supercritical CO2 extraction and anaerobic digestion. (15th November 2022) - Zhao, Weizhong; Su, Xianbo; Xia, Daping; Hou, Shihui; Wang, Qian; Zhou, Yixuan
Abstract: Coal reservoir is considered as the ideal site for coalbed methane (CBM) occurrence, biomethanation and CO2 sequestration. Four coal samples with different ranks were selected to conduct supercritical CO2 (Sc-CO2 ) extraction and anaerobic digestion (AD). X-ray photoelectron spectroscopy, mercury intrusion, and isothermal adsorption experiments were performed on the raw coal samples and the remaining coal samples after Sc-CO2 and Sc–CO2 –AD to analyze the mechanism of enhanced CBM recovery by reservoir modification. The results showed that coal pore volume and porosity are greatly increased after Sc-CO2 extraction. Meanwhile, the reduction of the oxygen-containing functional groups and the micropore specific surface area determined the weakening of the adsorption capacity of coal. After Sc–CO2 –AD, the macropore volume and porosity of coal continued to increase, and the permeability of coal was effectively improved. And the oxygen-containing functional groups and micropore specific surface area continued to decrease, which determined that the adsorption capacity of coal for methane continued to decrease. Sc-CO2 and AD can mutually promote the modification of coal reservoirs. These effects are quite favorable for gas desorption, migration and production during CBM exploitation, which provide powerful supports for CO2 emission reduction, CO2 geological sequestration and CBM production enhancement. Graphical abstract: Image 1 Highlights: Sc-CO2 experiment is conducted at simulated coal reservoir conditions. The biomethane yield of different rank coals is increased after Sc-CO2 treatment. Methane adsorption capacity of coal after Sc-CO2 treatment is decreased. Sc–CO2 –AD can improve porosity and pore connectivity of coal. A conceptual model is proposed to enhance CBM production based on Sc–CO2 –AD.